Parenting Patterns and Study Habits on Mathematics Learning Outcomes of Fifth-Grade Elementary School Students - Diani, Ni Putu Suardiani; Gusti Ngurah Sastra Agustika (MIMBAR PGSD Undiksha, 2023)
Parents play an important role in the child's learning process. The choice of parenting style applied at home also has an important role in the student learning process. This study aims to analyze the effect of parenting style and study habits on the mathematics learning outcomes of fifth-grade elementary school students. This research is ex-post-facto research. The sample in this study amounted to 124 students. Determination of the sample in this study using a random sampling technique. The method used in this study is a questionnaire. The analysis used in this study is simple regression and multiple regression. The results showed no effect between authoritarian parenting styles on student learning outcomes at 4.4%. There is an influence between parenting parents in the democratic category on student learning outcomes at 5.4%. There is no influence between the parenting style of permissive parents and student learning outcomes of 3.3%. There is an influence between study habits and student learning outcomes of 5.7%. Based on these results, it can be concluded that the parenting style of parents in the authoritarian, democratic, and permissive categories and students' learning habits significantly affect the results of learning mathematics for fifth-grade elementary school students.